Group videoconferencing intervention “C@nnected” to enhance maternal sensitivity in primary care in Chile: A feasibility trial - Victoria Binda; Marcia Olhaberry; Carla Castañon; Constanza Abarca; Catalina Caamaño; Javier Moran-Kneer (Cambridge Prisms: Global Mental Health)
Early interventions supporting parental sensitivity have proven effective. Despite advancements in telemedicine, research on remote group parenting interventions remains limited. This study evaluated the feasibility and acceptability of “C@nnected,” a brief group videoconferencing intervention aimed at enhancing maternal sensitivity in mother–infant dyads in primary care settings in Santiago, Chile. A feasibility randomized controlled trial (RCT) was conducted using quantitative and qualitative methods. Of 44 mother–infant dyads randomized, 26 were assigned to receive the intervention, whereas 18 were allocated to the control group. Eligibility and recruitment rates were 89% and 36%, respectively, with adherence at 50% and follow-up at 64.5%. The intervention demonstrated high acceptability in both the quantitative and qualitative evaluations. Mothers who participated in the intervention showed high scores in credibility and expectancy and reported increased knowledge, stronger bonds with their children and greater satisfaction and competence in their motherhood role. This pilot study underscores the potential of “C@nnected” while identifying areas for improvement. The findings provide valuable insights into refining and further evaluating its efficacy through an RCT.